Prophetic Communication and Religious Moderation: A Hadith-Based Model for Social Harmony in Plural Societies - Siagian, Darmansyah; Mailin, Mailin; Arifin, Zainal (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2025)
Religious extremism remains a persistent challenge in plural societies, requiring communication-based approaches that are both socially grounded and normatively legitimate. This study examines how a hadith-based religious moderation communication strategy, drawing on selected traditions from Ṣaḥīḥ al-Bukhārī, is implemented to prevent and address religious extremism in Labuhanbatu, Indonesia. Employing a descriptive qualitative field study, data were collected through semi-structured interviews with eight key informants representing the Ministry of Religious Affairs, the Indonesian Ulama Council, religious extension workers, lecturers, and community leaders, complemented by participatory observation and document analysis. The study applies a grounded theory approach involving initial coding, categorical clustering, and analytical filtering to identify dominant patterns of moderation communication. The findings reveal a three-pillar model of hadith-based moderation communication. First, qaulan karima functions as a preventive strategy through community-based religious moderation programmes initiated by the Ministry of Religious Affairs. Second, qaulan layyina operates as a dialogical mechanism to reduce tension and manage potential conflict, particularly through inter-institutional and interfaith dialogue facilitated by the Indonesian Ulema Council. Third, qaulan sadida serves as an intervention-oriented approach, enabling flexible mediation and rehabilitative communication in situations of escalating religious tension. This integrative communication model has contributed to reducing social polarisation and strengthening tolerance without promoting theological relativism. The study contributes to dakwah and social-religious communication scholarship by conceptualising hadith-based moderation as a practical communication framework for preventing extremism in plural social contexts.